Bonding with nature: a validation of the dispositional empathy with nature scale in Italy - Lovati, Chiara; Manzi, Federico; Di Dio, Cinzia; Massaro, Davide; Gilli, Gabriella; Marchetti, Antonella (Frontiers in Psychology, 2025)
This study proposes a psychometric validation of the Italian version of the Dispositional Empathy with Nature (DEN). Scientific research data has found high levels of environmental concern among people around the world, showing that majority of the population is aware of the seriousness of the environmental problems we are witnessing, as well as is conscious of the damage that some of their behaviors cause to the environment. Based on this premise, Empathy with Nature could be an important educational strategy for addressing the environmental crisis. A study was conducted involving 307 Italian adults (CFA = 146; 45.9% women; 54.1% man; Mean age = 34.65; SD = 11.770); (EFA = 161; 50.3% women; 49.7% man; Mean age = 34.30; SD = 10.360) to o assess the psychometric properties of a scale in the Italian context. The study aimed to establish the internal consistency of the DEN scale and evaluate its convergent, discriminant, and predictive validity. Both confirmatory and exploratory factor analyses, using a split sample, supported the one-factor structure consistent with the original version proposed by Tam. These findings strongly suggest that the DEN scale is reliable and valid in the Italian context.